Human peripheral CD4+ Vdelta1+ gamma delta T cells can develop into alpha beta T cells - Ziegler, Hendrik; Welker, Christian; Sterk, Marco; Haarer, Jan; Rammensee, Hans-Georg; Handgretinger, Rupert; Schilbach, Karin (Frontiers in Immunology, 2014)
The lifelong generation of alpha beta T cells enables us to continuously build immunity against pathogens and malignancies despite the loss of thymic function with age. Consequently, alpha beta T-cell development has to occur independently of the thymus. However, the sites and mechanisms of extrathymic T-cell development are not yet understood in detail. gamma delta T cells represent a small fraction of the overall T-cell pool, and are endowed with tremendous phenotypic and functional plasticity. gamma delta T cells that express the Vdelta1 gene segment are a minor population in human peripheral blood but predominate in epithelial (and inflamed) tissues. Here, we characterize a peripheral Vdelta1+ gamma delta T-cell subpopulation that expresses stem-cell and progenitor markers and is able to develop into functional alpha beta T cells ex vivo in a simple culture system and in vivo. The route taken by this process resembles thymic T-cell development. However, it involves the reorganization of the Vdelta1+ gamma delta TCR into the alpha beta TCR as a consequence of TCR-gamma chain downregulation and the expression of surface Vdelta1+Vbeta+ TCR components which we believe function as surrogate pre-TCR. This transdifferentiation process is readily detectable in vivo in inflamed tissue. Our study provides a conceptual framework for extrathymic T-cell development and opens up a new vista in immunology that requires adaptive immune responses in infection, autoimmunity and cancer to be reconsidered.